Comorbid Internalizing and Externalizing Disorders Predict Lability of Negative Emotions Among Children With ADHD. Issue 14 (December 2020) - Leaberry, Kirsten D.; Rosen, Paul J.; Fogleman, Nicholas D.; Walerius, Danielle M.; Slaughter, Kelly E.
Objective: A subset of children with ADHD experience more frequent, sudden, and intense shifts toward negative emotions. The current study utilized ecological momentary assessment (EMA) to provide a valid assessment of the impact of comorbid internalizing and externalizing disorders on negative emotional lability (EL) among children with ADHD.Method: Parents of 58, 8- to 12-year-old children with ADHD were administered a diagnostic interview to assess for ADHD and for the presence of comorbid disorders. Parents completed EMA-based ratings of their child's negative emotions three times daily for a total of 28 days.Results: Children with a comorbid internalizing disorder or children with comorbid oppositional defiant disorder (ODD) experienced significantly greater EMA-derived negative EL than children without comorbid disorders over time. Children with multiple comorbidities experienced greater EL than children with single comorbidities.Conclusion: Overall, this study suggested that both comorbid ODD and comorbid internalizing disorders contribute to negative EL among children with ADHD.